Correlation Between Gait Parameters and Physiological Cost Index in Healthy Indian Females - Sharma, Harshita; Sarkar, Aparna (International Journal For Research In Health Sciences And Nursing, 2016)
Objective: To analyze the correlation between Physiological Cost Index and the Gait Parameters and demographics. Participants: A convenience sample of 24 healthy females, age 25 to 50 years. Intervention: For the purpose of arriving at the Physiological Cost Index, after measuring the resting vitals, subject was instructed to walk to and fro the walkway at self-selected speed, wearing an ambulatory heart rate meter for measuring the heart rate at regular intervals. For gait parameters, the patient was asked to first dip her foot in hypoallergenic colour solution and then walk on a paper walk way to arrive at main outcome measures values such as step length, stride length, and base of support. Result: Mean age was 33.9±8.248 years. Mean height of the subjects was 155.2 ± 5.414 cm. Mean weight was 58.3 ±12.855 kg, mean BMI was 23.86±4.996 kg/m2 , mean stride length, was 94.7 ±10 cm, mean antero-posterior length was 23.29 ± 1.552 cm, mean lateral width of base was 21.86 ± 1.876 cm, toe out was 14.71 ± 2.594 degrees, and mean PCI was 0.4435 beats per meter. A Pearson correlation between the studied variables and PCI was found to be strongly correlated with the anteroposterior length, moderately positively correlated with weight, height, BMI, step length, stride length, toe out angle, and lateral width of base of the individual. There was a mild negative correlation between PCI and age. Conclusion: Physiological cost of walking in normal Indian females is directly associated with the weight, height, BMI, and gait parameters of the individual.